Flexible field-effect transistors with a high on/off current ratio based on large-area single-crystal graphene. (15th August 2020) - Ning, Jing; Wang, Ying; Feng, Xin; Wang, Boyu; Dong, Jianguo; Wang, Dong; Yan, Chaochao; Shen, Xue; Wang, Xinran; Zhang, Jincheng; Hao, Yue
Abstract: Large-area single-crystal graphene (LSG) over half a millimeter were synthesized via chemical vapor deposition, and a flexible ion gel-gated graphene field-effect transistor (FET) was fabricated to explore the electrical properties of the graphene based on the mechanism of electronic double layers. A procedure of cyclical oxidation/hydrogen-annealing processes by chemical vapor deposition (CVD) was proposed and optimized as a new growth method for the large single-crystal graphene, to facilitate the reconstruction of copper foil surface. To form a flexible FET on the polyethylene terephthalate substrate, LSG was utilized as a channel layer, and a spin-coated ion gel film was used as a gate dielectric. The flexible device demonstrates excellent electrical properties and high degree of bendability. When the device was bent by 8.1%, the on/off current ratio exceeded 400 because the deformation of the graphene crystal lattice widened graphene's bandgap. This work is a fundamental study on the growth mechanism of LSG and the two-dimensional-material-based ion gel-gated transistor for application in flexible electronic devices. Graphical abstract: Image 1